Intervención del terapista respiratorio en paciente masculino de 9 años de edad con bronquitis aguda. - Rodríguez Rodríguez, Moisés Guillermo (2022)
Acute bronchitis today is one of the main complications in the health of children, as epidemiological data we have acute respiratory infections in developing countries represents between 35% and 58% in pediatric patients, it is expected that each child suffers from 3 to 6 times this disease in the year. The clinical case was based on the intervention of the respiratory therapist in a 9-year-old male patient with acute bronchitis, the patient presents a clinical picture characterized by unquantified thermal rise, cough and respiratory distress. The general objective of this clinical case is to establish the appropriate respiratory therapy techniques in a 9-year-old male patient diagnosed with acute bronchitis. Respiratory therapy techniques used in patients with acute bronchitis are intended to clear the airways without causing injury and to prevent complications. In addition, these techniques, such as the administration of oxygen and nebulizations, are complemented by the pharmacological treatment that is administered in patients with acute bronchitis.